ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH AKUISI (Pada Perusahaan Sektor Mining and Mining Service yang Terdaftar di BEI yang Melakukan Aktivitas Akuisisi Periode 2008-2013) - Damar Putri Firdaus; Rodhiyah Rodhiyah (Universitas Diponegoro, 2017)
The acquisitions strategy are considered to create synergy and value-added. The success of acquisition can be seen from the company's performance, especially its financial performance. This research aims to analyze the comparison before and after acquisition on the company's financial performance mining and mining service sector in IDX. The company's financial performance is measured using financial ratios are: Liquidity Ratio, Solvency Ratio, Activity Ratio and Profitability Ratio.The research’s type is comparative research by comparing 2 years before and 2 years after acquisition. Sampling technique used is purposive sampling, where there are 10 companies as sample. Used secondary data. Aanalysis method used is normality test One-Sample Kolmogorov-Smirnov Test and then use different test Paired Sample t-test for normal distribution of data and Wilcoxon Signed Rank test for normally distributed data.The results from different test with a significance level of 5% showed no differences in Liquidity Ratio used CR as result sig 0,344 > 0,05. There’s difference in Solvency Ratio used DR as result sig 0,008 < 0,05 and used DER as result sig 0,020 < 0,05. There’s no difference Activities Ratio used TATO as result sig 0,141 > 0,05. There’s difference Profitability Ratio used NPM as result sig 0,019 < 0,05 ; ROI as result sig 0,001 < 0,05 ; ROE as result sig 0,001 < 0,05 dan EPS as result sig 0,008 < 0,05.The conclusion there are difference in solvency ratios and profitability ratios, there are no difference in the liquidity ratio and the ratio of the activity. Company needs to improve its current assets to current liabilities guarantee, restricting the use of funds from the loan, using its assets more efficiently and optimize the company's operations as well as the efficiency of the company in order to achieve satisfactory results.